Development of a New Generic Analytical Modeling of AC Coupling Losses in Cable-in-Conduit Conductors - Louzguiti, Alexandre; Zani, Louis; Ciazynski, Daniel; Turck, Bernard; Duchateau, Jean-Luc; Torre, Alexandre; Topin, Frederic; Bianchi, Marco; Ricchiuto, Anna Chiara; Bagni, Tommaso; Anvar, Valiyaparambil Abdulsalam; Nijhuis, Arend; et al. (IEEE transactions on applied superconductivity, 2018)
Coupling losses induced in cable-in-conduit conductors (CICC) when subject to a time-varying magnetic field are a major issue commonly encountered in large fusion tokamaks (e.g., JT-60SA, ITER, DEMO). The knowledge of these losses is crucial to determine the stability of CICC but is yet difficult to achieve analytically (thus in a short computation time) given the specific and complex architecture of these conductors although numerical solutions such as THELMA and JACKPOT already exist. In an attempt to ease the resolution of this problem, we have previously presented a theoretical generic study of a group of elements twisted together (representing a cabling stage of a CICC) and derived the analytical expression of its coupling losses. We have now extended this study to a two cabling stage conductor by establishing an analytical model to calculate its coupling losses as function of its effective features. In a second part, we compare our results to these of THELMA and JACKPOT on geometries representing ITER CS and JT-60SA TF conductors. Finally, we have set up a specific algorithm to reconstruct strand trajectories from X-ray images and have extracted the effective geometrical parameters of a JT-60SA TF conductor. Our next objective is then to extract its effective electrical parameters from interstrand resistivity measurements to be able to compare the coupling losses predicted by our analytical model with those measured within the SULTAN facility.